A study on slug induced stresses using file-based coupling technique - Mohmmed, A.O. (Asian Research Publishing Network, 2016)
Cyclic stresses imposed on the piping system are the potential cause of severe fatigue damage and failure. These stresses are induced due to pressure fluctuations which occurred as result of the slug flow motion inside the pipe. In this study, a coupled Fluid-Structure Interaction approach based on file coupling technique between the CFD code for the flow domain and the Finite Element Analysis code for the structure domain was utilized to address the induced stresses on the structural pipe. Three cases of air-water have been investigated and the CFD results reveal that the slug frequency and slug velocity increased with increasing the water velocity while the slug length decreased with increasing the water velocity. On the other hand, the maximum principal stresses increased by 10.2 and 23.7 when the slug velocity increased from 2.26 m/s to 3.39 m/s respectively. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.